Microbial Product Act As a Probiotic against Human Intestinal Pathogens - Vinothkumar, Dr.P (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Bacteriocins produced by L.acidophilus (LAB) have been in focus of many investigations because of their particular importance in dairy industry. Antibacterial activity of the isolated LAB (cell free filtrate) was tested against selected gram positive and gram negative bacterial species by well diffusion assay. Bacteriocin produced by L.acidophilus was showed higher antibacterial activity against gram negative pathogenic bacteria, such as E.coli, K.pneumoniae, S.typhimurium and V.cholerae. Whereas gram positive pathogenic bacteria showed lower antibacterial activity against S.aureus and B. cereus. The results obtained in the present study suggest that bacteriocin produced by L.acidophilus inhibits the growth of selected gram positive and gram negative bacterial sp. Regular consumption of probiotic food will prevent gastrointestinal infection in adult.